Go back to face-to-face classes? Writing opinion letters with feedback through written comments in eighth grade schoolchildren - Arancibia Gutiérrez, Beatriz Magaly; Retamal Rivera, Claudia (Lenguas Modernas, 2022)
The purpose of this study is to analyze the effectiveness of an adaptive and inclusive writing didactic sequence with feedback provided by written comments. The discursive genre of the learning object was the opinion letter. This experience was carried out in the context of COVID-19 pandemic online classes by the Language teacher and the Special Educational Needs teacher of two eighth grades classes of the town of Lota, collaboratively. Following a quasi-experimental design, one class received written comments at the margins of the previously mentioned fragment, while the other was provided with letter type comments, underneath the students’ written texts. And analytic rubric was used for assessment. The results show that regardless of the type of comments, both groups improved significantly. Moreover, through an appreciation scale students valued the experience positively, particularly in regards to collaborative work, as well as the opportunity to improve, receive comments and the chance to feel more prepared to write opinion letters in future assignments.